Sex-based differences of the impact of aortic valve calcium score on mortality and post-procedural outcomes after trans-catheter aortic valve replacement. (3rd October 2022) - Ahsan, M; Taskesen, T; Putz, J; Ugwu, J; Latif, A; Park, A; De Santis, T; Sigurdsson, G; Shivapour, D; McAllister, D; Chawla, A; Bhatt, D; et al.
Abstract: Introduction: Sex based differences exist in the presentation, outcomes, and management of cardiovascular diseases. Although aortic valve calcium (AVC) score has been postulated to be associated with post-procedural outcomes after transcatheter aortic valve replacement (TAVR), data on the impact of AVC score on procedural outcomes after TAVR based on sex have been scarce. Objective: The aim of the present study was to elucidate sex related differences in the prognostic impact of AVC score as a predictor of post-procedural outcomes and mortality in patients with severe aortic stenosis (AS) who underwent TAVR. Methods: We retrospectively abstracted the records of 497 patients with severe AS who underwent TAVR between January 2016 and July 2019 at our institution. All patients underwent a non-contrast cardiac CT scan on a Siemens Somatom Definition Flash 128 slice scanner. AVC score using the Agatston method was calculated retrospectively. Primary outcome was 1-year mortality. Patients were divided into two groups: 1) Non-severe AVC score group [women <1200 Agatston unit (AU) and men <2000 AU]; 2) Severe AVC Score group [women >1200 AU and men >2000 AU]. Cox-regression model was used to predict effect of variables on 1-year mortality in male and female patients. Results: Among 466 patients included, 268 patients were male and 198 were female (57.5% vs 42.5%). When compared with males, female patients had significantly lower AVC score (p<0.001), aortic valve area (AVA) (p<0.001), obstructive CAD (p<0.001), and history of previous PCI (p<0.004), and CABG (<0.001) but had a significantly higher STS score (6.7±3.2 vs 5.8±3.3 P=0.01). There was no difference between need for permanent pacemaker (PPM) implantation (11% vs 9.6%, p=0.4), major complications (16% vs 15%, p=0.9), stroke (0.8% vs 1.6%, p=0.7), 30-day (3.7% vs 4%, p=0.9), and 1-year mortality (14% vs 12%, p=0.6) between males and females, respectively. Female patients required smaller bio-prosthetic valves compared with males (26±3.2 vs 30±3, p<0.001). Cox regression analysis for female patients showed BMI, hemoglobin level, and AVA independently predicted 1-year mortality, while there was no impact of severe AVC score (>1200 AU) on 1-year mortality in females. Similarly, Cox regression analysis for male patients showed there was no impact of severe AVC score (>2000 AU) on 1-year mortality in males. When males in the severe AVC group were compared with female patients in the severe AVC group, there was no difference in 30 day (4.3% vs 3.3%, p=0.82) and 1-year mortality (14.2% vs 13.3%, p=0.77). Similarly, in the severe AVC group there was no difference between need for PPM implantation (12.8% vs 12.1%, p=0.9), major complications (19.7% vs 15.8%, p=0.4), and stroke (2.2% vs 1%, p=0.6) between males and females, respectively. Conclusion: There were no sex differences in the impact of AVC score on mortality and post-procedural outcomes after TAVR. Funding Acknowledgement: Type of funding sources: None.